Analysis Factors of Contraceptive Utilization on Women Of Child Bearing Age in Bengkulu City - Elza Wulandari; Pitri Subani; Yuni Ramadhaniati; Susilo Wulan (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Types of contraception in Indonesia generally are still directed on Non - Long acting reversible contraceptives method such as contraceptive injection and pill. Meanwhile government contraceptive program polices more directing on LARC contraceptive utilization like IUD, MOP, and MOW. The purpose of this study is to study factors associated with contraceptive utilization, LARC and Non-LARC on women of child bearing age in Bengkulu city. Time study was on August to October 2020. Population of these studies were women of child bearing age in primary health center Bengkulu city, years 2018 as many as 114,577. Samples are taken by proportional probability sampling technique from 20 Primary Health Centers in Bengkulu City as many as 110 persons. Data analysis is using chi-square test an Odd ratio test. The result of this study showed that there is relationship between education and contraceptive utilization by P-Value 0.019 and OR 3.147. there is no relationship between knowledge an contraceptive utilization on by P-Value 0.005, there is relationship between age and contraceptive utilization by P-Value 0.036 and OR 2.788, there is relationship between spousal support and contraceptive utilization by P-Value 0.011 and OR 3.42. Hoped health staff be able to increase the socialization of family planning program to women of child bearing age by health education.